The temporal communication behaviors of global software development student teams - Swigger, Kathleen; Hoyt, Matthew; Serçe, Fatma Cemile; Lopez, Victor; Alpaslan, Ferda Nur (Computers in Human Behavior, 2012)
Abstract: This paper examines the global software development process by using content analysis techniques, as described in an earlier study (), to determine time-variant patterns of communication behaviors among student teams engaged in a global software development project. Data gathered from two software development projects involving students in the US, Panama, and Turkey were used to determine how globally distributed team behavior is temporally patterned in complex ways. A formal, quantitative methodology for time variant analysis of the transcripts of global software student teams based on content analysis is established. Results from the analysis suggest a positive correlation between a team’s temporal communication patterns and project outcomes as well as a relationship between variations in communication behaviors and different phases of the software development cycle. The research also found that the temporal variations in communication behaviors between software phases were similar for the two projects. Such findings are intended to strengthen the case for developing new temporal measures for analyzing groups and teams.